2011
DOI: 10.1088/0004-637x/733/2/123
|View full text |Cite
|
Sign up to set email alerts
|

The Wolf-Rayet Content of M33

Abstract: Wolf-Rayet stars (WRs) are evolved massive stars, and the relative number of WC-type and WN-type WRs should vary with metallicity, providing a sensitive test of stellar evolutionary theory. The observed WC/WN ratio is much higher than that predicted by theory in some galaxies but this could be due to observational incompleteness for WN-types, which have weaker lines. Previous studies of M33's WR content show a galactocentric gradient in the relative numbers of WCs and WNs, but only small regions have been surv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
164
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 76 publications
(171 citation statements)
references
References 76 publications
7
164
0
Order By: Relevance
“…However, unlike our newly-found WR of WO-type, the majority (11 out of 12) of the new stars presented in BAT99 are of WN-type. This is to be expected since, as discussed in Neugent & Massey (2011), the strongest emission feature in WCs is nearly 4× stronger than the strongest line in WNs (Conti & Massey 1989), making WNs much more difficult to detect. Therefore before BAT99, the ratio of un-detected WRs in the LMC was previously skewed towards WNs.…”
Section: Wolf-rayet Stars In the Large Magellanic Cloudmentioning
confidence: 75%
“…However, unlike our newly-found WR of WO-type, the majority (11 out of 12) of the new stars presented in BAT99 are of WN-type. This is to be expected since, as discussed in Neugent & Massey (2011), the strongest emission feature in WCs is nearly 4× stronger than the strongest line in WNs (Conti & Massey 1989), making WNs much more difficult to detect. Therefore before BAT99, the ratio of un-detected WRs in the LMC was previously skewed towards WNs.…”
Section: Wolf-rayet Stars In the Large Magellanic Cloudmentioning
confidence: 75%
“…While WN and WNh stars are expected to be systematically different (Crowther 2007;Smith & Conti 2008), this approach eases the comparison between the two galaxies. In M33, the Neugent & Massey (2011) catalogue only contains one WNh star. However, Hamann, Gräfener & Liermann (2006) listed many WNh stars in the Milky Way, providing circumstantial evidence that they should also exist in larger numbers in M33; one star in the Neugent & Massey (2011) catalogue is labeled "H-rich" but not classified WNh; one of the classification sources (Abbott et al 2004) intentionally omitted the Smith, Shara & Moffat (1996) WNh criteria; and one WN7h star from another source (Drissen et al 2008) is simply reported as a WN7 in Neugent & Massey (2011).…”
Section: Resultsmentioning
confidence: 99%
“…It takes more time to reach deeper layers, and consequently these layers bear the imprint of the nucleosynthesis occurring at later stages of evolution. Neugent & Massey (2011) showed that the ratio WC/WN is correctly reproduced by the models of Meynet & Maeder (2003) at low metallicity. This is not the case at higher metallicity (see also Neugent et al 2012) where evolutionary models predict too few WC stars.…”
Section: Introductionmentioning
confidence: 82%